Social creativity and phenomenon of success in postindustrial society. Issue 2 (2nd July 2016) - Stoletov, Anatoliy
Abstract : The article deals with the problem of mutual relations between the social creativity and the substance of success. This problem is analyzed with reference of contemporary conceptions of social reality which unite objective and subjective aspects of the society and make accent on the complex and dynamic its character. Such approach leads to idea that success means capability to change social space and time. The success creates a new point of attraction not only by success itself but also by future possibility. The success in postindustrial society obtains the symbolic form more than material. The direction of the social mobility in case of success may be not only vertical. These transformations are the process of social creativity.